'Feminization of migration': the implications for 'left-behind' families in Ghana. (2nd January 2022) - Apatinga, Gervin Ane; Kyeremeh, Emmanuel K.; Arku, Godwin
ABSTRACT: Research suggests that in sub-Saharan Africa, independent transnational female migration is highly prevalent. Despite this prevalence, scholarship on those who are left behind in the migration process largely focuses on women, and there is little research focusing on transnational female migration and the families these women leave behind. Using a qualitative approach, with the push-pull theory and the new household economics of labour migration framework to examine female migration and its impact on left-behind families in Ghana, this study fills a valuable research gap in the migration literature. Twelve in-depth interviews were purposively held with men whose spouses were residing overseas. Findings from the thematic analysis revealed that independent female migration is a common occurrence in the Ghanaian context. Social, economic and cultural opportunities were some of the reasons the respondents identified for the prevalence of transnational female migration. While respondents associated transnational female migration with certain benefits, they explained that it has short-and long-term consequences, including reverse remittances, marital instability and effects on children's subjective well-being. While the results corroborate the key arguments of the push-pull theory and the new household economics of labour migration framework, which suggest that multiple factors trigger migration, they demonstrate the need for effective planning and careful decision making among spouses in the migration process.